Ehrlichia chaffeensis and Its Invasin EtpE Block Reactive Oxygen Species Generation by Macrophages in a DNase X-Dependent Manner - Omid Teymournejad (American Society for Microbiology, 2017)
ABSTRACT The obligatory intracellular pathogen Ehrlichia chaffeensis lacks most genes that confer resistance to oxidative stress but can block reactive oxygen species (ROS) generation by host monocytes-macrophages. Bacterial and host molecules responsible for this inhibition have not been identified. To infect host cells, Ehrlichia uses the C terminus of its surface invasin, entry-triggering protein of Ehrlichia (EtpE; EtpE-C), which directly binds the mammalian cell surface receptor glycosylphosphatidylinositol-anchored protein DNase X. We investigated whether EtpE-C binding to DNase X blocks ROS production by mouse bone marrow-derived macrophages (BMDMs). On the basis of a luminol-dependent chemiluminescence assay, E. chaffeensis inhibited phorbol myristate acetate (PMA)-induced ROS generation by BMDMs from wild-type, but not DNase X−/−, mice. EtpE-C is critical for inhibition, as recombinant EtpE-C (rEtpE-C)-coated latex beads, but not recombinant N-terminal EtpE-coated or uncoated beads, inhibited PMA-induced ROS generation by BMDMs from wild-type mice. DNase X is required for this inhibition, as none of these beads inhibited PMA-induced ROS generation by BMDMs from DNase X−/− mice. Previous studies showed that E. chaffeensis does not block ROS generation in neutrophils, a cell type that is a potent ROS generator but is not infected by E. chaffeensis. Human and mouse peripheral blood neutrophils did not express DNase X. Our findings point to a unique survival mechanism of ROS-sensitive obligate intramonocytic bacteria that involves invasin EtpE binding to DNase X on the host cell surface. This is the first report of bacterial invasin having such a subversive activity on ROS generation. IMPORTANCE Ehrlichia chaffeensis preferentially infects monocytes-macrophages and causes a life-threatening emerging tick-transmitted infectious disease called human monocytic ehrlichiosis. Ehrlichial infection, and hence the disease, depends on the ability of this bacterium to avoid or overcome powerful microbicidal mechanisms of host monocytes-macrophages, one of which is the generation of ROS. Our findings reveal that an ehrlichial surface invasin, EtpE, not only triggers bacterial entry but also blocks ROS generation by host macrophages through its host cell receptor, DNase X. As ROS sensitivity is an Achilles’ heel of this group of pathogens, understanding the mechanism by which E. chaffeensis rapidly blocks ROS generation suggests a new approach for developing effective anti-infective measures. The discovery of a ROS-blocking pathway is also important, as modulation of ROS generation is important in a variety of ailments and biological processes.